2017
DOI: 10.1515/helia-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Embryogenesis from Corolla Tubes of Interspecific Amphiploids between Cultivated Sunflower (Helianthus annuus L.) and Its Wild Species

Abstract: Somatic embryogenesis in vitro provides an efficient means of plant multiplication, facilitating sunflower improvement and germplasm innovation. In the present study, using interspecific amphiploids (2n=4x=68) between cultivated sunflower and wild perennial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…This showed that the somatic embryo development process is asynchronous. Similar results have been found in Hibiscus sabdariffa (Konar et al 2018), Akebia trifoliata (Zou et al 2019), Helianthus annuus L. (Fu et al 2017), and Capsicum baccatum (Venkataiah et al 2016). Finally, when the cotyledonary stage embryos were sub-cultured in MS medium containing 1 mgL -1 BAP at 12 WAC, they were converted into complete plantlets (Figure 1.G).…”
Section: Induction Of Embryogenic Calli Developmentsupporting
confidence: 84%
“…This showed that the somatic embryo development process is asynchronous. Similar results have been found in Hibiscus sabdariffa (Konar et al 2018), Akebia trifoliata (Zou et al 2019), Helianthus annuus L. (Fu et al 2017), and Capsicum baccatum (Venkataiah et al 2016). Finally, when the cotyledonary stage embryos were sub-cultured in MS medium containing 1 mgL -1 BAP at 12 WAC, they were converted into complete plantlets (Figure 1.G).…”
Section: Induction Of Embryogenic Calli Developmentsupporting
confidence: 84%